How Olya Died and Folklore Was Born - Archipova, Aleksandra (Tautosakos darbai, 2019)
The subject of discussion in this article comprises the ways in which a literary piece becomes folklore. In order to elucidate this, the author discusses a poem by Aleksey Apuchtin “The Madman” written in 1890, and its folksong versions. The original story depicting a farther and his daughter perishing under suspicious circumstances turns into a story of a girl killed by her lover. In the first decades of the 20th century, this poem encountered immense popularity in Russia, including its frequent recitations under musical accompaniment and repeated screenings. Therefore, it is plausible to assume that similar folklore variants may have occurred independently, affected by typological folklore regularities, as well as by the well-known “proto-text” (songs from the movies). If folklorization of an individual work is a purposeful process, it can be defined and even guided in a sense by the necessity of folklore as a cliché: the literary piece turns into folklore only when a certain folkloric counterpart is found for every literary motive or image. There is no other way for such literary image or motive to become folklore. This process requires changes on all the textual levels, including lexical, semantic, and pragmatic ones. The folklore stereotypization narrows the field of semantic valence to the minimum collection of associations. This makes one of the essential differences between folklore and literature, ensuring comparatively stable transmission of the folklore texts in the course of time, and granting that the poem by Apuchtin finds its way into the folklore language only bearing the connotations approved by the “folklore censorship”. Lay opinion is prone to perceive such folklorized text of Vosilkos (‘The Cornflowers’) as an original poem by Apuchtin.